Effects of community youth teams facilitating participatory adolescent groups, youth leadership activities and livelihood promotion to improve school attendance, dietary diversity and mental health among adolescent girls in rural eastern India (JIAH trial): A cluster-randomised controlled trial - Komal Bhatia; Suchitra Rath; Hemanta Pradhan; Subhashree Samal; Andrew Copas; Sumitra Gagrai; Shibanand Rath; Raj Kumar Gope; Nirmala Nair; Prasanta Tripathy; Kelly Rose-Clarke; Audrey Prost (Elsevier, 2023)
Objectives: To evaluate whether and how community youth teams facilitating participatory adolescent groups, youth leadership and livelihood promotion improved school attendance, dietary diversity, and mental health among adolescent girls in rural India. Design: A parallel group, two-arm, superiority, cluster-randomised controlled trial with an embedded process evaluation. Setting, intervention and participants: 38 clusters (19 intervention, 19 control) in West Singhbhum district in Jharkhand, India. The intervention included participatory adolescent groups and youth leadership for boys and girls aged 10-19 (intervention clusters only), and family-based livelihood promotion (intervention and control clusters) between June 2017 and March 2020. We surveyed 3324 adolescent girls aged 10-19 in 38 clusters at baseline, and 1478 in 29 clusters at endline. Four intervention and five control clusters were lost to follow up when the trial was suspended due to the COVID-19 pandemic. Adolescent boys were included in the process evaluation only. Primary and secondary outcome measures: Primary: school attendance, dietary diversity, and mental health; 12 secondary outcomes related to education, empowerment, experiences of violence, and sexual and reproductive health. Results: In intervention vs control clusters, mean dietary diversity score was 4·0 (SD 1·5) vs 3·6 (SD 1·2) (adjDiff 0·34; 95%CI -0·23, 0·93, p = 0·242); mean Brief Problem Monitor-Youth (mental health) score was 12·5 (SD 6·0) vs 11·9 (SD 5·9) (adjDiff 0·02, 95%CI -0·06, 0·13, p = 0·610); and school enrolment rates were 70% vs 63% (adjOR 1·39, 95%CI 0·89, 2·16, p = 0·142). Uptake of school-based entitlements was higher in intervention clusters (adjOR 2·01; 95%CI 1·11, 3·64, p = 0·020). Qualitative data showed that the community youth team had helped adolescents and their parents navigate school bureaucracy, facilitated re-enrolments, and supported access to entitlements. Overall intervention delivery was feasible, but positive impacts were likely undermined by household poverty. Conclusions: Participatory adolescent groups, leadership training and livelihood promotion delivered by a community youth team did not improve adolescent girls' mental health, dietary diversity, or school attendance in rural India, but may have increased uptake of education-related entitlements. Trial registration: ISRCTN17206016